Pengembangan E-LKPD Berbasis Experimental Method Materi Peristiwa Alam untuk Meningkatkan Literasi Sains Peserta Didik Kelas V SD - Heri Dermawan; Rena Fadilah Malik; Anggi Riafadilah (STIT Fatahillah, 2024)
Developing E-LKPD (Electronic Student Worksheets) based on experimental methods is an important innovation in science education, especially to increase the scientific literacy of fifth-grade elementary school students. This research explores the effectiveness of using E-LKPD in improving understanding of natural event material, increasing student involvement, and stimulating interest in learning about science. The research method uses a literature review. The literature review results show an increased understanding of natural event material after using E-LKPD. The interactivity provided by E-LKPD helps increase student involvement in learning, while the use of technology in learning also triggers students' interest in science. Benefits for teachers were also found, with the evaluation feature integrated with E-LKPD allowing them to monitor student progress in real-time and provide more appropriate guidance. These findings show that experimental method-based E-LKPD has great potential in increasing scientific literacy at the elementary level.